The connection of employees' motivation and company's innovation process : Case study within technology industry - Mytty, Noora (My University, 2020)
In today’s rapidly changing business world, the importance of employees as a crucial factor in companies’ innovativeness should not be underestimated and it requires a better understanding to be able to benefit fully from the workforce. Thus, it has been studied how companies can internally take advantage of their motivated employees, when it comes to improving performance within innovations. The purpose of this thesis was to find a possible connection between employees’ motivation and the company’s innovation process. Furthermore, motivation was treated in two separate types, extrinsic and intrinsic, throughout the thesis. In order to fulfill the purpose, it was necessary to find out which motivational characteristics lead into successful results and where the employees recognize themselves in the innovation process. A case study was conducted in an innovative company operating within the technology industry to get actual insight into the employees’ motivation and its possible connection to the innovation process. Several studies exist of motivation and innovation, but mainly those studies connect intrinsic motivation to innovation. Therefore, there was a need to conduct a study where both motivational types are included. Five managerial level employees were interviewed in face-to-face semi-structured interviews in a time frame of one month and important data was collected regarding their motivation and position in the innovation process. Purpose of the thesis could be fulfilled as it was found out in the case company that a combination of employees’ motivation is connected with the company’s idea generation stage of their innovation process. Finally, theoretical implications and practical contributions were presented, and also certain limitations of the present research introduced and suggestions for further study were given.

Nykypäivän nopeasti muuttuvassa yritysmaailmassa työntekijöiden tärkeyden ymmärtäminen yritysten innovatiivisuudessa tulisi ottaa huomioon sekä ymmärtää se paremmin, jotta työvoimaa osattaisiin hyödyntää oikein. On myös tutkittu, että yritykset voivat sisäisesti hyötyä motivoituneista työntekijöistään, kun kyse on uusien innovaatioiden saavuttamisesta. Tämän pro gradu -työn tavoitteena oli löytää mahdollinen yhteys työntekijöiden motivaation ja yrityksen innovaatioprosessin välillä. Tämän lisäksi motivaatiota käsiteltiin kahdessa eri motivaatiotyypissä, ulkoisessa ja sisäisessä, läpi koko tutkimuksen. Jotta tutkimuksen tavoite saatiin täytettyä, oli tärkeää selvittää, mitkä motivaation tunnusmerkit johtavat onnistuneisiin tuloksiin ja missä innovaatioprosessin vaiheessa työntekijät tunnistavat itsensä. Case-tutkimus toteutettiin teknologia-alalla toimivassa innovatiivisessa yrityksessä, jotta todellinen käsitys voitiin muodostaa työntekijöiden motivaatiosta ja sen mahdollisesta yhteydestä innovaatioprosessiin. Motivaatiosta ja innovaatiosta on tehty monia tutkimuksia, mutta nämä tutkimukset yhdistävät pääasiassa sisäisen motivaation ja innovaation. Tämän takia oli tarve tehdä tutkimus, jossa molemmat motivaatiotyypit otetaan huomioon. Viittä johtotason työntekijää haastateltiin henkilökohtaisilla puolistrukturoiduilla yksilöhaastatteluilla yhden kuukauden aikana ja tärkeää tietoa kerättiin liittyen heidän motivaatioonsa ja asemaansa innovaatioprosessissa. Pro gradu -työn tavoite saatiin täytettyä, sillä case-yrityksessä saatiin selvitettyä, että motivaatiotyyppien yhdistelmä on yhteydessä yrityksen ideointivaiheeseen heidän innovaatioprosessissaan. Lopuksi tutkimuksen teoreettiset ja käytännön arvot esiteltiin ja tietyistä tutkimuksen rajoituksista keskusteltiin sekä annettiin ehdotuksia lisätutkimukselle aiheesta.
Keywords: Motivation, extrinsic motivation, intrinsic motivation, innovation, innovation process